Further characterization of the PhoP regulon: identification of new PhoP-activated virulence loci. - Belden, W J (Infect Immun, 1994)
Salmonella typhimurium survival within macrophages is an essential virulence property necessary to enteric fever pathogenesis. This survival requires coordinate transcriptional activation of virulence genes within acidified macrophage phagosomes. Virulence gene transcription is regulated by a two-component system comprising the PhoP (transcriptional activator) and PhoQ (sensor-kinase) proteins. Thirteen new PhoP-activated loci (designated pagD to pagP) encoding membrane or secreted proteins have been identified by use of the transposon TnphoA. Three of these loci have a chromosomal location that was linked to the previously identified pagC locus. Strains with TnphoA insertions in pagD, pagJ, pagK, and pagM were significantly attenuated for mouse virulence (50% lethal dose greater than 1,000 times that of wild-type bacteria). No strains with pag::TnphoA insertions were found to have altered sensitivity to the cationic antimicrobial peptide NP-1 defensin. PhoP and PhoQ are pleotropic regulators of membrane or secreted proteins, suggesting that the ability to effect a global change in the expression of these proteins is required for S. typhimurium survival within acidified macrophage phagosomes. IMAGES: